Pengaruh Physical Evidence, Kualitas Layanan, Dan Atmosfer Yang Dipersepsikan Terhadap Niat Kunjungan Kembali di Sorake Beach Walk - Telaumbanua, Ernina (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the effect of physical evidence, service quality, and perceived atmosphere on return visit intentions at Sorake Beach Walk. The research method used is a quantitative approach by distributing questionnaires to 200 respondents who have visited the destination. The collected data were analyzed using multiple linear regression techniques to determine the relationship between the independent and dependent variables. The results showed that the three factors had a significant effect on return visit intentions. Physical evidence has the most dominant influence, followed by service quality and perceived atmosphere. Adequate facilities, responsive service, and a supportive atmosphere overall create a positive experience for visitors, which in turn increases their intention to return. The conclusion of this study is that Sorake Beach Walk managers should pay attention and improve aspects of physical evidence, service quality, and perceived atmosphere holistically to maintain visitor loyalty and increase destination attractiveness.